The Improving Speaking Skills Using Quizizz Media and Project Based Learning Model For 9th Graders - Misbahun Haidir Firmansyah; Siti Azizah; Muharlisiani, Lusy Tunik (CV. Kalimasada Group Profesional, 2023)
This study investigates the effectiveness of Quizizz media and project-based learning model in improving English speaking skills. The research, executed at SMPN 3 Surabaya, encompassed a cohort of 33 students in the ninth grade and utilized a classroom action research methodology. The structure of the investigation was delineated into three segments: a pre-intervention stage, Cycle I, and Cycle II. Preliminary observations indicated the students' speaking proficiencies to be sub-optimal. Noticeable advancements in proficiency were recorded during Cycle I; however, certain inaccuracies remained consistent across evaluative dimensions. In Cycle II, significant enhancements were evident, with a predominant fraction of the student population achieving the stipulated Minimum Completion Criteria (KKM) score. Feedback solicited from students predominantly underscored the superiority of the integrated approach in comparison to conventional pedagogical techniques. The findings underscore the potential of combining Quizizz media with a project-based learning framework as an instrumental mechanism for ameliorating students' speaking abilities. However, this study recognizes inherent constraints, notably the limited sample dimension and an exclusive emphasis on speaking proficiencies. Subsequent investigations are recommended to discern the versatility of the combined Quizizz media and Project Based learning approach in varied linguistic competencies and pedagogical environments.